2007
DOI: 10.1509/jmkg.71.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Can A Retail Web Site be Social?

Abstract: Avatars are lifelike characters created by technology. Research suggests that avatars can increase the persuasiveness of online sales channels. The authors investigate how the social cues inherent in avatars influence consumers' affect and shopping value. In Study 1, social cues induce perceptions of Web site socialness, leading to increased pleasure and arousal, both of which positively influence flow, hedonic and utilitarian value, and patronage intentions. Study 2 finds that social cue-induced arousal leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
423
0
23

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(499 citation statements)
references
References 62 publications
26
423
0
23
Order By: Relevance
“…The existing body of knowledge also includes numerous publications related to website design (15 %) (e.g., Arazy et al 2010;Ganley 2011;Gottschlich et al 2013;Li and Buchthal 2012;Macaulay et al 2007;Mackenzie et al 2009;Noh et al 2013;Shi et al 2013;Wang et al 2007;Yue and Jiang 2013;Zhang and Liu 2013;Zhu et al 2010). Social shopping websites (82 %), presentation sites (12 %), and virtual worlds (6 %) were the social media platform types primarily investigated.…”
Section: Research Theme: Website Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing body of knowledge also includes numerous publications related to website design (15 %) (e.g., Arazy et al 2010;Ganley 2011;Gottschlich et al 2013;Li and Buchthal 2012;Macaulay et al 2007;Mackenzie et al 2009;Noh et al 2013;Shi et al 2013;Wang et al 2007;Yue and Jiang 2013;Zhang and Liu 2013;Zhu et al 2010). Social shopping websites (82 %), presentation sites (12 %), and virtual worlds (6 %) were the social media platform types primarily investigated.…”
Section: Research Theme: Website Designmentioning
confidence: 99%
“…Several articles in this research stream explore how to motivate, enhance, and support the interaction of consumers by applying collaborative shopping technologies (e.g., virtual advisors, avatars, social recommender systems), which support navigation and communication and impact consumers' shopping value (e.g., Arazy et al 2010;Gottschlich et al 2013;Hess et al 2009;Li and Buchthal 2012;Seedorf et al 2014;Shi et al 2013;Wang et al 2007;Yue and Jiang 2013;Zhu et al 2010). For instance, Seedorf et al (2014) explore social co-browsing for shoppers, a relatively recent social technology for collaborative online shopping, and how this technology impacts user engagement.…”
Section: Research Theme: Website Designmentioning
confidence: 99%
“…Wang et al (2007) suggest that the use of "social cues" (i.e. language, social role, voice, interactivity) by virtual retailers yields a competitive advantage that provides consumers with enhanced perceptions of human connection and the formation of emotional bonds; social applications induce perceptions of web site sociality, leading to increased pleasure and arousal, both of which positively influence flow, hedonic and utilitarian value, and patronage intentions.…”
Section: Engaging Social Media For Personalizing the Customer's Onlinmentioning
confidence: 99%
“…The broad scope of research into this construct has shown that socialness within an interface can be readily perceived, whether the technology is a simple text-based interface or a technologically rich set of components including pictorial representation, natural language processing and other artificial intelligence capabilities [45,72,74]. It has been previously used to study consumers' shopping experiences with online providers [75,76] or face-to-face market transactions [77].…”
Section: Agarwal and Prasadmentioning
confidence: 99%